The effect of inflation, US bond yield, and exchange rate on Indonesia bond yield - Achlanudin Yusuf; Ahmad Danu Prasetyo (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Indonesia sovereign bonds are investment graded bonds, therefore, it will have global exposure and it will be more interlinked with global market condition. The purpose of this research is to examine the impacts of US bond yield, exchange rate, and inflation on Indonesian bond yield. Our result conclude that based on Vector Error Correction Model there are long run causality from inflation, US 10 year bond yield, and USD/IDR exchange rate to Indonesia 10 year bond yield. There are also short-run causality from inflation and US 10 year bond yield to Indonesia 10 year bond yield. Based on impulse response function, Indonesia 10 year bond yield respond permanently to changes in US 10 year bond yield. Based on Granger causality we also reveal that inflation and US 10 year bond yield can cause Indonesia 10 year bond yield. US 10 year bond yield has a larger impact than inflation when it comes to affecting Indonesia 10 year bond yield